Optimizing growth : predictive and profitable strategies to understand demand and outsmart your competitors - Green, Jason, 1963-; Henneman, Mark, 1961-; Antov, Dimitar, 1978- (Findaway World : Gildan Audio, 2018)
Optimizing Growth is a handbook for how to succeed in the age of big data. Today's business environment looks dramatically different than it did even a decade ago, and it continues to evolve at an increasing rate; macroeconomic shifts, consumer trends, technological advances, and changing competitive dynamics are accelerating the pace of change, and businesses are struggling to grow amidst the turbulence. This book provides insightful guidance, real-world success stories and practical tools to achieve growth in this new era, utilizing big data to achieve a deeper understanding of demand, customers, competitors, and opportunity. With disruption around every corner, growth now demands innovative new approaches and an improved capacity to meet customer needs; by gaining a stronger grasp of demand, businesses can elevate performance from "survive" to "thrive." Develop a deeper understanding of your business's growth factors. Re-sync your thinking to gain greater leverage against disruption. Delve deeper into demand, and boost fulfillment capabilities. Capture more growth opportunities using precision analytics frameworks